Getting to the Top of Mind: How Reminders Increase Saving - Karlan, Dean; McConnell, Margaret; Mullainathan, Sendhil; Zinman, Jonathan (Management Science, 2016)
We provide evidence from field experiments with three different banks that reminder messages increase commitment attainment for clients who recently opened commitment savings accounts. Messages that mention both savings goals and financial incentives are particularly effective, whereas other content variations such as gain versus loss framing do not have significantly different effects. Nor do we find evidence that receiving additional late reminders has an additive effect. These empirical results do not map neatly into existing models, so we provide a simple model where limited attention to exceptional expenses can generate undersaving that is in turn mitigated by reminders. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2015.2296 . This paper was accepted by Teck-Hua Ho, behavioral economics.